Changes of TSPO-mediated mitophagy signaling pathway in learned helplessness mice. (30th November 2016) - Li, Dongmei; Zheng, Ji; Wang, Mingyang; Feng, Lu; Ren, Zhili; Liu, Yanyong; Yang, Nan; Zuo, Pingping
Abstract: Low response rate was witnessed with the present monoaminergic based antidepressants, urging a need for new therapeutic target identification. Accumulated evidences strongly suggest that mitochondrial deficit is implicated in major depression and 18 kDa translocator protein (TSPO) plays an important role in regulating mitochondrial function. However the changes of TSPO and TSPO mediated mitophagy pathway in the depressive brain is unclear. In present study, a well validated animal model of depression, learned helplessness (LH), was employed to investigate the relevant changes. Significant behavioral changes were observed in the LH mice. Results showed that TSPO and other mitophagy related proteins, such as VDAC1, Pink1 and Beclin1 were significantly decreased by LH challenge. Moreover, KIFC2, relevant to the mitochondrial transport and Snap25, relevant to neurotransmitter vesicle release, were also obviously down-regulated in the LH mice, which further rendered supportive evidence for the existing mitochondrial dysfunction in LH mice. Present results demonstrated that LH induced depressive symptoms and affected TSPO-mediated mitophagy pathway, indicating a potential target candidate for depression treatment. Highlights: TSPO expression significantly decreased in the brain of LH mice. Several TSPO downstream mitophagy signal molecules were also down-regulated. TSPO may be potential therapeutic target for depression treatment.